The chronology and canon of Ælfric of Eynsham - Kleist, Aaron J. (Anglo-Saxon studies, 2019)
A thousand years and more ago, with Vikings ravaging the coastlines and the millennium drawing nigh, a monk named Ælfric embarked on studies that would make him the most erudite, prolific, and influential author writing in English before Chaucer. What drove Ælfric was no desire to leave his mark on history, however, but the belief that he held a treasure on which the temporal and eternal welfare of his contemporaries depended: knowledge of the rich moral teachings of the early Christian church. What he produced was an astonishing synthesis of some of the finest minds in history, conveyed with remarkable authorial transparency and an elegantly simple style. While there is much we know about Ælfric, both from his own self-disclosure and the wealth of surviving manuscripts containing work by him, there is also much that muddies the waters: his feverish pace of simultaneous composition, his habit of reshaping and repurposing his writings, the staggering complexities of textual transmission, and competing scholarly interpretive voices. This volume seeks to take it all into account, setting forth a comprehensive picture of work and the manuscripts in which it may be found. Integrating scholars' best understanding to date and framing new avenues for inquiry, it offers a launching point for new research into this pivotal figure of early England. AARON J KLEIST is Professor of English at Biola University